A Korovkin theorem in multivariate modular function spaces - Carlo Bardaro; Ilaria Mantellini (Journal of Function Spaces and Applications)
In this paper a modular version of the classical Korovkin theorem in multivariate modular function spaces is obtained and applications to some multivariate discrete and integral operators, acting in Orlicz spaces, are given.